Kinetic modeling of the fixed bed column adsoption of Pb(II), CU(II) and Ni(II) from ternary metal ion solution using chitosan coated bentonite - Bermillo, Hanna Lee P. (College of Engineering, University of the Philippines Diliman, 2014)
Industrial wastewaters contain several heavy metals, which if not treated properly before disposal will have detrimental effects on health and the environment. Batch and column adsorption studies previously conducted by different investigators have proven the ability of chitosan-coated bentonite (CCB) in removing a wide variety of heavy metals from aqueous solution. However, column adsorption of multi-metal systems using CCB is yet to be established. In this study, simultaneous adsorption of Pb (II), Cu (II) and Ni (II) ions onto CCB was carried out in a fixed bed column. The effects of bed height, flow rate and initial metal ion concentration on breakthrough time, exhaustion time and equilibrium adsorption capacity were investigated. The individual and total equilibrium adsorption metal capacities improved with decreasing flow rate and increasing bed height and initial metal ion concentration. Maximum total equilibrium adsorption capacity of 35.9 mg/g was achieved when initial concentration of the metal ions, bed height and flow rate were 200 mg/L, 2.0 cm and 0.4 ml/min, respectively. On the other hand, the breakthrough time and exhaustion time increased with decreasing initial metal ion concentration and flow rate and increasing bed height. Experimental breakthrough curves were in good agreement (R2>0.85 and %ε<50%) with Bohart-Adams, Thomas and Yoon-Nelson kinetic models. The Fourier transform infrared(FTIR) results confirmed that the amino and hydroxyl groups of chitosan served as binding sites for the metal ions. This study demonstrates the effectiveness of CCB as adsorbent for the removal of Pb (II), Cu (II) and Ni (II) from a ternary metal solution. CCB has the potential for use as a PRB material for remediating groundwater containing ternary metal. The service life of CCB will depend on the pollutant which has the lowest affinity for CCB.